PENGARUH KOMPETENSI DAN KEDISIPLINAN GURU TERHADAP PRESTASI SISWA SMPN 3 BANTUGA KECAMATAN AMPANA TETE - Ridwan, Ridwan; Idrus, Idrus; Gulom, Muhamad; Kadir, Abdul; Qosim, Nanang; Hasan, Hasan (Fakultas Ekonomi Universitas Alkhairaat, 2022)
The purpose of this study was to determine the effect of teacher competence and discipline on student achievement at SMPN 3 Bantuga, Ampana Tete District, either partially or simultaneously. This research is a verification research. According to Riduwan (2006; 55) verification research is a study that analyzes the influence of one variable with another variable. The number of respondents in this study were 37 respondents, and the analytical tool used was multiple linear regression. The conclusion of this study is, both simultaneously and partially the competence and discipline of teachers have a significant effect on student achievement at SMPN 3 Bantuga, Ampana Tete District. Keywords: Competence, Discipline, Student Achievement